PENGEMBANGAN MEDIA PEMBELAJARAN KARTU REMI FISIKA PADA POKOK BAHASAN ALAT-ALAT OPTIK DI SMA - Ainul Kiromah; Trapsilo Prihandono; Maryani Maryani; Muhammad Lutfi Helmi; Siti Nur Laila (Universitas Jember, 2022)
Abstract This type of research is an R&D (Research & Development) research using the ADDIE design which includes analyze, design, development, implementation, and evaluation. This research was tested using two classes, namely class XI MIPA 1 with 30 students and class XI MIPA 2 with 29 students at SMAN Plus Sukowono. This study aims to test the validity, effectiveness, and practicality of the learning media of playing physics playing cards on the subject of optical instruments. The instruments in this study used validation sheets, learning activity assessment rubrics, implementation sheets, and student response questionnaires. The results of the analysis of the research succeeded in sharpening the minds of students in understanding learning without feeling bored. The application of learning media for playing physics playing cards succeeded in making students understand the material given. This is evident from the results of the validation, the results of the effectiveness of the media, and the results of the practicality of the media which state that physics playing cards are suitable for use during learning. Key Word: learning media development, physics playing card